Improving Citrus Nitrogen Uptake Efficiency: Understanding Citrus Nitrogen Requirements - Kelly T. Morgan; Edward A. Hanlon (EDIS)
This publication is one in a series of three looking at improved citrus nutrition by increasing the efficiency of fertilizer use. The objectives of this document are: 1. To better match citrus tree N requirements at selected life stages with fertilization practices based on tree growth; 2. To explain the demands for fertilization by citrus trees recovering from leaf loss caused by storms, insects, or disease; 3. To relate citrus nutrient uptake efficiency (NUE) as a means to improve or maintain productivity while minimizing ground and surface water pollution.  This document is SL-240, one of a series of the Department of Soil and Water Sciences, UF/IFAS Extension. Original publication date April 2006.